Germylene–sulfoxide as a potential hemilabile ligand: application in coordination chemistry12. Issue 44 (22nd October 2018) - Lentz, Nicolas; Mallet-Ladeira, Sonia; Baceiredo, Antoine; Kato, Tsuyoshi; Madec, David
Abstract : Heteroleptic organogermylenes containing a sulfoxide donor function were used for application in coordination chemistry with [W(cod)(CO)4 ], [Mo(nbd)(CO)4 ] and [Ru(PPh3 )3 Cl2 ]. Abstract : We describe here the synthesis of heteroleptic organogermylenes containing a sulfoxide donor function for their application in coordination chemistry. While complexation reaction with [W(cod)(CO)4 ] and [Mo(nbd)(CO)4 ] afforded bis(germanium)(ii ) transition-metal complexes, a bidentate complex coordinated by germanium(ii ) and the oxygen atom of the sulfinyl group was obtained from [Ru(PPh3 )3 Cl2 ].